The Oxford guide to library research - Mann, Thomas 1948- (Oxford Univ. Press, 2015)
The information world has undergone drastic changes since the publication of the 3rd edition of The Oxford Guide to Library Research in 2005, and Thomas Mann, a veteran reference librarian at the Library of Congress, has extensively revised his text to reflect those changes. This book will answer two basic questions: First, what is the extent of the significant research resources you will you miss if you confine your research entirely, or even primarily, to sources available on the open Internet? Second, if you are trying to get a reasonably good overview of the literature on a particular topic, rather than just "something quickly" on it, what are the several alternative methods of subject searching--which are not available on the Web--that are usually much more efficient for that purpose than typing keywords into a blank search box, with the results displayed by relevance-ranking computer algorithms? This book shows researchers how to do comprehensive research on any topic.